2018
DOI: 10.1080/14786451.2018.1559164
|View full text |Cite
|
Sign up to set email alerts
|

Towards the EU emissions targets of 2050: optimal energy renovation measures of Finnish apartment buildings

Abstract: Towards the EU emissions targets of 2050: Optimal energy renovation measures of Finnish apartment buildings Member countries of the European Union have released targets to reduce carbon dioxide emissions by 80% by the year 2050. Energy use in buildings is a major source of these emissions, which is why this study focused on the cost-optimal renovation of Finnish apartment buildings. Apartment buildings from four

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 20 publications
1
83
0
Order By: Relevance
“…This study found the ground-source heat pump to be the most effective way to reduce emissions in Finnish detached houses. This is similar to the results obtained in the previous study concerning Finnish apartment buildings [13]. The result relies strongly on the low emission factor of the Finnish energy system.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study found the ground-source heat pump to be the most effective way to reduce emissions in Finnish detached houses. This is similar to the results obtained in the previous study concerning Finnish apartment buildings [13]. The result relies strongly on the low emission factor of the Finnish energy system.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike in the previous study focusing on apartment buildings [13], additional thermal insulation of external walls was a common renovation option. The unit costs in the case of detached houses were estimated lower than with apartment buildings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-five pre-determined retrofit packages were calculated using quasi-steady state equations in the DEAP software, a web-based tool for producing Building Energy Ratings. In the Finnish context, energy retrofits have been examined for apartment buildings [10,11], where both primary energy demand and CO 2 emissions could be significantly reduced cost-effectively, especially using heat pumps, but also including improvements to the building envelope. In Finnish office buildings CO 2 emissions could be cost-effectively reduced by 50% while preserving thermal comfort [12].…”
Section: Introductionmentioning
confidence: 99%